Evaluating carbon-electrode dielectrophoresis under the ASSURED criteria - Martinez-Duarte, Rodrigo; Mager, Dario; Korvink, Jan G.; Islam, Monsur (Frontiers in Medical Technology, 2022)
Extreme point-of-care refers to medical testing in unfavorable conditions characterized by a lack of primary resources or infrastructure. As witnessed in the recent past, considerable interest in developing devices and technologies exists for extreme point-of-care applications, for which the World Health Organization has introduced a set of encouraging and regulating guidelines. These are referred to as the ASSURED criteria, an acronym for Affordable (A), Sensitive (S), Specific (S), User friendly (U), Rapid and Robust (R), Equipment-free (E), and Delivered (D). However, the current extreme point of care devices may require an intermediate sample preparation step for performing complex biomedical analysis, including the diagnosis of rare-cell diseases and early-stage detection of sepsis. This article assesses the potential of carbon-electrode dielectrophoresis (CarbonDEP) for sample preparation competent in extreme point-of-care, following the ASSURED criteria. We first discuss the theory and utility of dielectrophoresis (DEP) and the advantages of using carbon microelectrodes for this purpose. We then critically review the literature relevant to the use of CarbonDEP for bioparticle manipulation under the scope of the ASSURED criteria. Lastly, we offer a perspective on the roadmap needed to strengthen the use of CarbonDEP in extreme point-of-care applications.